2012
DOI: 10.1111/j.1365-2133.2012.11018.x
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells and alopecia: a review of pathogenesis

Abstract: Recent work has focused on the hair follicle as the main source of multipotent stem cells in the skin. The hair follicle bulge contains multipotent stem cells that can form the epidermis, hair follicles and sebaceous glands and help in repopulation of the epidermis after injury. The localization of these stem cells to the bulge area may explain why some types of inflammatory alopecia cause permanent loss of hair (cicatricial alopecia) (such as lichen planopilaris and discoid lupus erythematosus), while others … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…LPP is characterized by follicular hyperkeratosis, perifollicular erythema, and a loss of follicular orifices [1, 5]. The underlying pathophysiology is not fully understood and appears to be multicausal; while there is evidence that the loss of positive stem cells for CK15 (cytokeratin 15) leads to LPP [6, 7], there is also scientific agreement that T lymphocytes appear to influence unknown antigens of keratinocytes and destroy these cells. It is further assumed that pharmacologic substances, contact allergens, or infectious substances might trigger the emergence and maintenance of LPP.…”
Section: Introductionmentioning
confidence: 99%
“…LPP is characterized by follicular hyperkeratosis, perifollicular erythema, and a loss of follicular orifices [1, 5]. The underlying pathophysiology is not fully understood and appears to be multicausal; while there is evidence that the loss of positive stem cells for CK15 (cytokeratin 15) leads to LPP [6, 7], there is also scientific agreement that T lymphocytes appear to influence unknown antigens of keratinocytes and destroy these cells. It is further assumed that pharmacologic substances, contact allergens, or infectious substances might trigger the emergence and maintenance of LPP.…”
Section: Introductionmentioning
confidence: 99%
“…Exploration of the literature data on development of scarring alopecia led us to the understanding that clones C8⁄144B and LHK15 of anti-CK15 antibodies are mostly used [62], and LHK15 antibody, recognized as a marker for bulge epithelial stem cells in humans [63], was selected for this study. Other investigators have shown that bulge cells may serve as frame builders in the follicular construction of a hair [64], and the opinion that loss of stem cells in the bulge area of the hair follicle is the reason for alopecia has been established [7,22,23]. CK15 has been shown to be an early predictor of keratinocyte differentiation, directing it to become either epidermal or follicular [19].…”
Section: Discussionmentioning
confidence: 99%
“…A further controversy is added by Cotsarelis' publication reporting about the migration of the bulge cells to the interfollicular epidermis [21]. Moreover, an inflammatory cellular infiltrate, located in the bulge region and distal follicle, may become a strong contributor to deficiency of hair follicle stem cells in LPP, explaining the permanent loss of hair (cicatricial alopecia) occurring in LPP [22]. Mobini et al suggested that damage of eHFSCs evidenced by diminished or absent immunostaining of CK15 and mediated by cytotoxic CD8 positive cells plays a role in the pathogenesis of LPP [23].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et demonstrated that MSCs may contribute to the regeneration of skin during aging [29]. Several interesting studies have been done in the last few years to investigate the role of stem cells in alopecia [30]. Fukuoka et al demonstrated that hair regenerative therapy was effective for hair growth and is a potential alternative for hair regeneration in patients who are unwilling or unsuitable to undergo traditional surgical hair transplantation [31].…”
Section: Discussionmentioning
confidence: 99%